SMART-system: Past and future - Miyaji, C. (Procedia Engineering, 2010)
SMART-system is a video database developed by the Japan Institute of Sports Sciences (JISS). It was made available to all national sports federations (NSF) in 2007. As of January 2010, the system is being used by 12 NSF, it has 1107 registered users, and 48,153 archived video files. SMART-system 2.0 is a new version that evolved from the experiences of designing and managing the original system. The main features of the new system are, (1) enhanced scalability: the system is capable of handling large NFS archives and small personal videos, and (2) enhanced integration with other resources such as web page and graphics data: these resources will be displayed with the video synchronously. These new features will improve training and coaching activities.